ANALISIS TINGKAT KEPUASAN KONSUMEN PASAR AGUNG DENPASAR - widyanthi, ayu maha; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2013)
ABSTRACT The purpose of this study was to determine: (1) the level of consumer satisfaction grand market, and (2) differences in the level of consumer satisfaction views of social demography. Determination of the sample using a two-stage sampling method of judgment, respondents 200 people, with the 22 indicators measured using a Likert scale. Data were analyzed with descriptive analysis, cross tables and Chi Square test. Results showed not all consumers are satisfied, judging from the number of levels of suitability value less than 100 persen. The big difference in satisfaction based on demographic characteristics. Improved by optimizing the satisfaction indicators have a low percentage of satisfaction levels. Based on demographic characteristics, preferential treatment to consumers, male, age more than 30 years, low levels of education, and work. The difference in behavior is not expected to reduce the behavior of previous behavior towards consumers who are already satisfied. Keywords: traditional market, revitalization of the market, customer satisfaction, socio-demographic characteristics, chi square analysis
Keywords: traditional market; revitalization of the market; customer satisfaction; socio-demographic characteristics; chi square analysis